Organic Leadership - "Cole, Neil, 1960-" ("Grand Rapids, Mich. :")
Includes bibliographical references (p. 305-308) and index.
Keywords: CHRISTIAN LEADERSHIP.;LEADERSHIP -- RELIGIOUS ASPECTS -- CHRISTIANITY